Institut Agama Islam Negeri (IAIN) dan Pembangunan Etos Kerja Keilmuan - Juwaini Juwaini (Ar-Raniry: International Journal of Islamic Studies, 2014)
The development of information and communication technology has brought a change in materialism and pragmatism trend. Material satisfaction is increasingly becoming an obsession even at the sacrifice of his moral life. This phenomenon occurs not only in politics or government bureaucracy but also in a lot of education and college academic communities. In this regard, the efforts of revitalization work of ethic paradigm based on religious morality become important to be strengthened. The Expectation from this community effort is that the academic community base on intellectual integrity and academic honesty. This work ethic can be developed through moral and religious consciousness that work only to get Allah's approval.